ras and p53 in the prediction of survival in Dukes' stage B colorectal carcinoma - Bennett, M A (1995)
Aims—To determine possible associations between p53 allelic deletion, c-Ki-ras mutational activation, immunohistochemical detection of p53 and ras proteins, various clinicopathological variables, and patient outcome in 168 Dukes' stage B colorectal carcinomas. Methods—Allelic deletion at the p53 tumour suppressor gene locus was detected using polymerase chain reaction (PCR) based loss of heterozygosity (LOH) assays. Overexpressed proteins were detected using the CM1 polyclonal antibody. A PCR based assay was used to detect the presence of activating mutations at codon 12 of c-Ki-ras. Immunostaining was carried out using a monoclonal antibody to p21(ras). Results—p53 LOH, CM1 immunostaining, c-Ki-ras mutational activation, and p21(ras) immunostaining were not predictive of survival by logrank analysis. Multivariate analysis using Cox regression did not predict survival in this group of tumours. Conclusions—Aberrations in ras and p53 are unlikely to play an important role in the subdivision of patients with Dukes' stage B colorectal carcinoma into more accurate prognostic strata. It is possible that later genetic events are more important in conferring a specific phenotype on the resultant Dukes' stage B tumour.